STRATEGI MANAJEMEN KEPALA MADRASAH UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI MTS PONDOK PESANTREN BABUL KHAER BULUKUMBA - Sulaiman, Umar; Djafar, Hamsiah; Mihrani; Munawir, Ahmad; Mansur, Amiruddin (Institut Agama Islam Negeri (IAIN) Palopo, 2025)
The research aims to identify the management strategies implemented by the head of the madrasa to improve the quality of learning, understand the implementation of these management strategies in daily practices, and analyze the impact of these strategies on the quality of learning and student achievement. This study employs a descriptive research design. Data collection was conducted using interview guidelines, observation sheets, and documentation. The findings reveal that (1) the management strategies applied by the head of the madrasa to enhance learning quality include strategies for: improving teacher professionalism; optimizing the learning process; enhancing academic and non-academic achievements; fulfilling facilities and infrastructure; managing financing; fostering community relations; and conducting supervision and evaluation. (2) The implementation of management strategies by the head of the madrasa in daily practices includes: organizing regular study sessions and seminars; allowing teachers to take study leave for further education; optimizing extracurricular guidance; procuring appropriate and planned facilities and infrastructure; promoting discipline; and recognizing class rankings and overall performance. (3) The application of management strategies by the head of the madrasa positively impacts learning quality and student achievement, leading to improvements in teaching quality, increased discipline and performance among teachers, development of teacher competencies, motivation and appreciation for teachers, effective management of facilities and infrastructure, enhanced student achievements, innovative and sustainable learning practices, and strengthened collaboration with parents/guardians and the community. Keywords: Management Strategy, Quality of Learning, Madrasa.